Audit Sistem Informasi Aplikasi Fingerspot Wdv 204bnc di Sekolah Islam Menggunakan Cobit 5 - Sukirno, Agustiani; Zuraidah, Eva (TIN: Terapan Informatika Nusantara, 2024)
This research was conducted to identify and ensure that existing system procedures in the company function properly, using the Cobit 5 framework to audit the Fingerspot WDV 204BNC application information system in Islamic Schools using COBIT 5 with DSS03 and MEA01 domains and a comprehensive audit of the information system has never been carried out. used by the company so that the information system operational services cannot be ascertained whether or not they are by the school's standard needs. The information system audit on the Fingerspot WDV 204BNC application system running which is expected to run well according to the school's needs and objectives, with capability analysis. The audit results with the highest scores, namely the DSS03 domain, received a maturity level score of 8.55, and MEA 01 received a maturity level score of 13.91, with a Fully Achieved achievement score, all target levels have entered level 5 and the overall total maturity index score is 112.29 and maturity level is 22. .46, the average maturity index value is 56.15, while the capability maturity level is 11.23. From the results of the GAP analysis obtained from DSS03 and MEA01, it has reached the desired target level must be maintained, and must be improved further.